1991
DOI: 10.1083/jcb.114.2.337
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of bumetanide-sensitive Na+/K+/Cl- cotransport by different mitogens in synchronized human skin fibroblasts is essential for cell proliferation.

Abstract: Abstract. In this study, we examined the role of the bumetanide-sensitive Na+/K+/CI -cotransport in the mitogenic signal of human skin fibroblast proliferation . The Na+/K+/Cl -cotransport was dramatically stimulated by either fetal calf serum, or by recombinant growth factors, added to quiescent Go/Gt human skin fibroblasts . The following mitogens, FGF, PDGF, a-thrombin, insulin-like growth factor-1, transforming growth factor-a, and the phorbol ester, 12-0-tetradecanoyl-phorbol-13-acetate, all stimulated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 17 publications
7
40
0
Order By: Relevance
“…It was found that when cells were exposed to both amiloride and bumetanide, the mitogen-induced early increase in intracellular Na and DNA synthesis were both abolished, whereas nei ther inhibitor was completely effective by itself. The same workers reassessed the role of Na/K/2C1 cotransport in mitogenesis using primary cultures of normal diploid human skin fibroblasts [76]. In contrast with earlier work [68], bumetanide and furosemidc each caused a marked inhibition (50% or greater) o f mitogen-induced DNA synthesis, mea sured as pH]thymidine incorporation.…”
Section: Inhibition Ofn A/k /2c I Coiransport May Affect Cell Prolifementioning
confidence: 88%
“…It was found that when cells were exposed to both amiloride and bumetanide, the mitogen-induced early increase in intracellular Na and DNA synthesis were both abolished, whereas nei ther inhibitor was completely effective by itself. The same workers reassessed the role of Na/K/2C1 cotransport in mitogenesis using primary cultures of normal diploid human skin fibroblasts [76]. In contrast with earlier work [68], bumetanide and furosemidc each caused a marked inhibition (50% or greater) o f mitogen-induced DNA synthesis, mea sured as pH]thymidine incorporation.…”
Section: Inhibition Ofn A/k /2c I Coiransport May Affect Cell Prolifementioning
confidence: 88%
“…There are reports that mitogens stimulate functional NKCC activity (e.g., Refs. 8,47) and that overexpression of the NKCC protein will stimulate cell proliferation (48). In light of these findings, it is very interesting to note that HCMV infection stimulates the host cells to enter the cell cycle, but causes the cycle to halt at the G 1 /S interface (e.g., Refs.…”
Section: Hcmv Infection Of Mrc-5 Cells Leads To a Perinuclear Accumulmentioning
confidence: 99%
“…The dependence of an increase in proliferation on NKCC1 activation is indicated by the finding that this response is suppressed by bumetanide (Bildin et al, 2000). This association was described in human skin fibroblasts, in which stimulation of bumetanide-sensitive NKCC by different mitogens was shown to be essential for cell proliferation (Panet and Atlan, 1991), and the NKCC inhibitors-bumetanide and furosemide-were shown to inhibit cell proliferation (Panet et al, 1994). Additional evidence for the dependence of proliferation on amount of NKCC1 comes from the finding that gene overexpression augments cell proliferation in human skin fibroblasts (Panet et al, 2000).…”
Section: Discussionmentioning
confidence: 80%